The first confessor [compact disc, unabridged] : the legend of Magda Searus - Goodkind, Terry (Goodkind, Terry. Sword of truth., 2015)
Married to the powerful leader of her people, safe among those gifted with great ability, Magda Searus is protected from a distant world descending into war. But when her husband, a man who loved life and loved her, unexpectedly commits suicide, she suddenly finds herself alone. Because she is ungifted herself, without her husband she no longer has standing among her people, and she finds herself isolated in a society that seems to be crumbling around her.